New species of Parmularius hopwood and Damaliscus sclater and Thomas (Alcelaphini, Bovidae, Mammalia) from Makapansgat, and comments on faunal chronological correlation - Vrba, Elizabeth S. (Bernard Price Institute for Palaeontological Research, 1977)
Two new species of Alcelaphini, based on fossils from the Makapansgat Limeworks, are described. One is an early member species of the extinct genus Parmularius Hopwood. The present description is the first record of a Parmularius from any southern African fossil site. The other new species belongs to Damaliscus Sclater and Thomas, and is closely related to the extinct Damaliscus niro (Hopwood). The phylogenetic relationships of the new species to other extant and extinct alcelaphines are discussed. Comparison with fossils of the same, and/or related, species elsewhere in Africa gives rise to comments on faunal chronological correlation.
Main article
Keywords: Alcelaphini; Makapansgat; phylogeny